The equation 5/3x + 11/3 = -4/3 is solved as follows:
Multiplying both sides by 3 to clear the fractions, we get:
(3)(5/3x + 11/3) = (3)(-4/3)
5x + 11 = -4
Subtracting 11 from both sides:
5x = -4 - 11
5x = -15
Dividing both sides by 5:
x = -15 / 5
x = -3
Therefore, the solution is x = -3.
Note: I didn't see any numbers to fill in.
The equation 5/3x+11/3=−4/3 is solved as follows. Fill in the correct numbers to complete the solution.(1 point
53x+113=−43
53x=
Subtract 113 from both sides.
x=
Multiply both sides by 35, the reciprocal of 53.
1 answer